2008
DOI: 10.1200/jco.2007.14.4659
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study Comparing Exemestane With Tamoxifen As First-Line Hormonal Treatment of Metastatic Breast Cancer in Postmenopausal Women: The European Organisation for Research and Treatment of Cancer Breast Cancer Cooperative Group

Abstract: A B S T R A C T PurposeThis phase III randomized open-label clinical trial was designed to evaluate the efficacy and safety of the steroidal aromatase inactivator exemestane versus the antiestrogen tamoxifen as first-line treatment for metastatic breast cancer (MBC) in postmenopausal women. Patients and MethodsThe study was conducted at 81 centers and enrolled postmenopausal patients with measurable hormone-sensitive metastatic or locally advanced breast cancer. Prior adjuvant chemotherapy and/or tamoxifen wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
192
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(201 citation statements)
references
References 23 publications
(8 reference statements)
3
192
1
5
Order By: Relevance
“…Computer-generated randomisation methods were used in three studies, and only one study failed to report the methods used [45]. Similarly, concealment of allocation was used in three studies with only one study failing to adequately report their methods (PO25) [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer-generated randomisation methods were used in three studies, and only one study failed to report the methods used [45]. Similarly, concealment of allocation was used in three studies with only one study failing to adequately report their methods (PO25) [31].…”
Section: Resultsmentioning
confidence: 99%
“…The full network included 4 unique studies comparing tamoxifen (20 mg/day) to letrozole [31][32][33][34][35][36][37][38][39][40], anastrozole (TARGET [30,[41][42][43] and North American [29,44] studies), and exemestane [45][46][47][48][49][50][51][52]. One study comparing anastrozole to tamoxifen (40 mg/day) [53] was excluded because the dosage was incomparable to dosages of tamoxifen used in the other studies.…”
Section: Resultsmentioning
confidence: 99%
“…The HR for PFS seen in this 321 study (0·797) is similar to the improvement shown by third-generation AIs over Page 16 tamoxifen. [4][5][6][7][8] In addition to the primary endpoint results, pre-defined subgroup 323 analyses were performed. The test for heterogeneity was not statistically significant 324 across all the subgroups although it was noted that potential enhanced treatment 325 effects with fulvestrant vs anastrozole were seen in some subgroups, including 326 patients with non-visceral disease compared with visceral disease.…”
Section: Page 15mentioning
confidence: 99%
“…More recently, however, aromatase inhibitors have become widely used for the treatment of breast cancer in postmenopausal women. Studies comparing exemestane with tamoxifen for first-line hormonal therapy of metastatic breast cancer in postmenopausal women have shown that the incidence of hot flashes of any grade was slightly lower with exemestane (35.1%) than with tamoxifen (38.1%) [9,10]. This difference between aromatase inhibitors and tamoxifen was echoed in the Breast International Group (BIG) 1-98 and the Arimidex, Tamoxifen, Alone, or in Combination trials [11,12].…”
Section: Introductionmentioning
confidence: 97%